Thematic Hadith Methodology From Theory to Application (Genealogy, Conception, and Implementation) - Farida Nur ‘Afifah; M. Khoirul Hadi al-Asy ari (Universitas Islam Cordoba Banyuwangi, 2025)
This article discusses the methodological study of thematic hadits, both in the theory and application. The thematic hadith methodology is a way to understand hadith by collecting hadiths according to a theme or a topic of discussion so that, they are not confined to understanding just one hadith. Seeing the phenomenon of society in interpreting hadith textually and influencing people’s understanding hadith thematically. This article will describe the meaning, urgency, emergence and development, forms of thematic hadith. This study is included in the literature review. As for what is produced, thematic hadirh are traditions that have exited since of the Prophet Muhammad in oral form, and developed into special studies during the caliphate Umar bin Abdul Azis. Then, there are several thematic hadith forms including those based.